Disruptive Potentials of Digitalization on Business Models: Drivers, Challenges and Opportunities for Small and Medium-Sized Enterprises in The Service Sector in Rural Areas - Matthias VOGEL; Christophe SAID; Giuseppe STRINA (Communications of International Proceedings, 2022)
Small and medium sized enterprises (SMEs) occupy a special position within the German economy and the global trend towards digitization increasingly affects the business models of these companies. The successful transformation of analog business models requires a large number of resources that allow companies to prepare their business models for the future. However, not all companies have the same conditions since the ones in rural areas have to contend with various factors, including infrastructure problems, inadequate network coverage and a lack of skilled workers. Accordingly, this study will focuse on the question which disruptive effects digitization has on the business models of small and medium sized enterprises (SMEs) in the service sector in rural areas. A special focus will be placed on the opportunities, risks and challenges. The region of South Westphalia will be used as a model region for rural areas in the course of the survey. The study will examine the digital maturity of the companies as well as the assessment of disruptive effects on business models provided by various technologies. We also assume that the corona pandemic was a kind of enabler and accelerator for the integration of digital technologies into the business model of service SMEs.
Keywords: Small and medium sized enterprises; Business models; rural areas